Weight-Based Link Scheduling for Convergecast in WirelessHART Network. (14th July 2016) - Zhang, Kewang; Feng, Zhou; Li, Xin
WirelessHART is considered to be one of the most promising wireless network protocols for its high robustness comparing to other similar wireless networks. Convergecast is an efficient approach for industrial control. But in WirelessHART specifications, no scheduling algorithms are defined for convergecast. In this paper, an efficient link arrangement strategy for packet delivering named WBLSS (Weight-Based Link Scheduling Strategy) is proposed. In order to improve the communication reliability and assign time slots to nodes in the network evenly, WBLSS considers network topology for time slot assignment. Nodes with more children in the communication tree have more time slots for communication, which improves the global throughput dramatically. As compared to the existing link arrangement strategy in WirelessHART, both the throughput of the network and the real-time performance are improved in WBLSS.